2020
DOI: 10.3389/fmars.2020.00161
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With Icariin Affects Estrogen Synthesis, Vitellogenesis, and Oocyte Development in the Chinese Mitten Crab, Eriocheir sinensis

Abstract: In Eriocheir sinensis aquaculture, crabs feeding on an artificial diet without steroid hormones available in ice-fresh fish or snails show delayed ovarian maturation and late listing. Icariin (ICA), a safe plant-derived monomer compound, can effectively promote estradiol (E 2) synthesis and ovarian development in mammals, but its effect in crustaceans has not been reported. We investigated the effects of ICA on estrogen synthesis, vitellogenesis, and oocyte development in Chinese mitten crabs fed with one of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…Those tissues were frozen in liquid nitrogen immediately and stored at −70°C for further analysis. The gonadal somatic index (GSI) and hepatosomatic index (HSI) of the crab were calculated as the percentage of tissue wet weight to body wet weight (Zheng et al., 2020). The meat yield (MY) of the crab was calculated using the following formulae: MY (%) = 100 × muscle wet weight/body wet weight.…”
Section: Methodsmentioning
confidence: 99%
“…Those tissues were frozen in liquid nitrogen immediately and stored at −70°C for further analysis. The gonadal somatic index (GSI) and hepatosomatic index (HSI) of the crab were calculated as the percentage of tissue wet weight to body wet weight (Zheng et al., 2020). The meat yield (MY) of the crab was calculated using the following formulae: MY (%) = 100 × muscle wet weight/body wet weight.…”
Section: Methodsmentioning
confidence: 99%
“…The concrete formulation (Table S1), and processing flow of the diets, and the culture conditions and daily management are consistent with the previous description (Zheng et al, 2019). Our previous basic research showed that after 2 months' feeding trial, the growth of all juvenile crabs in each group entered into the key exogenous vitellogenic stage, but the ovarian development progress and nutrient deposition status between each group presented the difference, showing as the haemolymph E 2 contents, VTG contents and gonadosomatic indexes (GSIs) in ICA50 (E 2 = 71.72 pg/ml; GSI = 3.81%; VTG = 607.15 ng/ml) and ICA 100 (E 2 = 86.06 pg/ml; GSI = 4.65%; VTG = 635.61 ng/ml) crabs were significantly higher than those in the control (E 2 = 42.82 pg/ml; GSI = 2.02%; VTG = 486.18 ng/ml) (Zheng et al, 2020). In addition, the growth performance of crabs in each group showed difference (Zheng et al, 2019), showing as carbs in ICA 100 group had the highest final weight (FW = 72.93 g) and weight gain rate (WGR = 118.36%) compared with the control group (FW = 64.88 g; WGR = 92.93%).…”
Section: Ethics Statement Feeding Trail Design and Biochemical Measurementsmentioning
confidence: 73%
“…Icariin is the main flavonoid bioactive component in Epimedium (Li et al, 2015). According to the previous research results on the nutrition physiology of E. sinensis in our laboratory, icariin has the effects of antioxidation, enhancing immunity, promoting sex steroid hormone synthesis, vitellogenesis and ovarian nutrients deposition, suggesting that icariin has the potential to be used as a new functional feed additive in aquatic animals culturing (Zheng et al, 2019(Zheng et al, , 2020. Recent studies have shown that icariin has preventive and therapeutic effects on metabolic diseases such as diabetes, insulin resistance, obesity and dyslipidaemia (Li et al, 2020;Zheng et al, 2016;Aljehani et al, 2020;Wang, Gao, et al, 2020;Wang, Xiong, et al, 2020).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations